Short‐term impacts of COVID‐19 on food security and nutrition in rural Guatemala: Phone‐based farm household survey evidence - Ceballos, Francisco; Hernandez, Manuel A.; Paz, Cynthia (International Association of Agricultural Economists, 2021)
This article examines the short‐term effects of the COVID‐19 lockdown on food security and nutrition in rural Guatemala. We rely on a comprehensive panel dataset of 1,824 small agricultural households collected over two survey rounds, on November–December 2019 and May–June 2020. We place special emphasis on changes in agricultural and nonagricultural income sources, including remittances, and changes in dietary diversity, including consumption of animal source foods (ASF) and fruits and vegetables (F&V). We find that COVID‐19 affected the incomes, food security, and dietary patterns of households, with a decrease in ASF diversity and an increase in F&V diversity, and an overall net decrease in dietary diversity across all food groups. Dietary diversity among women in reproductive age, however, remained unchanged, and increased among children under 2 years old. Interestingly, households with relatively higher incomes appear to have reduced their dietary diversity to a larger extent than lower income ones, as well as households located in communities with more severe access restrictions. The focus of the study in a region with a high prevalence of poverty and chronic malnutrition provides an important perspective into the consequences of the lockdown in complex rural contexts with vulnerable populations and contributes to inform eventual recovery measures.